Stališča slovenskih učiteljev o vplivu integracije/ inkluzije na učence z različnimi vrstami posebnih potreb v osnovni šoli - Schmidt, Majda (Šolsko polje, 2011)
Numerous studies show that successful implementation of integration/inclusion of children with special needs largely depends on teachers' positive attitudes towards it. The empirical research presented in the main part of this article analyzes attitudes of a representative sample of Slovenian teachers (n = 1,360) regarding four domains of impact (the impact of inclusion on pupils with special needs, on peers, on teachers, and on the classroom environment. In this, we controlled the role of the following two relevant characteristics of the sample: the category of special needs (physical impairments, borderline intellectual abilities, learning difficulties, and behavioral/ emotional disorders) and the category of teacher' professional expertise in working with pupils with special needs. We used the Impact of Inclusion Questionnaire. The results show that teachers' attitudes towards integration/inclusion are determined by the type of special needs the integrated pupils have. Teachers expressed the highest level of consent in the case of pupils with physical impairments and the lowest in the case of pupils with behavioral and emotional disorders. Our study shows that, in addition to the type of special needs, teachers' professional expertise in working with pupils with special needs is another important factor that determines the level of agreement with integration/inclusion. It turned out that the teachers that had taken part in various forms of education and training had a more positive attitude towards all domains of impact.
Keywords: integracija; integration; inclusion; inkluzija; teachers' attitudes; učenci s posebnimi potrebami; učitelji; pupils with special needs; strokovna usposobljenost; various types of special needs; teachers' professional expertise; defektologija; učni dosežki; socialni dosežki